2014
DOI: 10.1111/mve.12051
|View full text |Cite
|
Sign up to set email alerts
|

High phylogenetic diversity of the cat flea (Ctenocephalides felis) at two mitochondrial DNA markers

Abstract: The cat flea, Ctenocephalides felis (Siphonaptera: Pulicidae) (Bouché), is the most common flea species found on cats and dogs worldwide. We investigated the genetic identity of the cosmopolitan subspecies C. felis felis and evaluated diversity of cat fleas from Australia, Fiji, Thailand and Seychelles using mtDNA sequences from cytochrome c oxidase subunit I (cox1) and II (cox2) genes. Both cox1 and cox2 confirmed the high phylogenetic diversity and paraphyletic origin of C. felis felis. The African subspecie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 33 publications
8
85
3
2
Order By: Relevance
“…A DNA extraction method described by Lawrence et al . [29] (S1 File) was employed that conserved the exoskeleton for downstream morphological identification.…”
Section: Methodsmentioning
confidence: 99%
“…A DNA extraction method described by Lawrence et al . [29] (S1 File) was employed that conserved the exoskeleton for downstream morphological identification.…”
Section: Methodsmentioning
confidence: 99%
“…Given the specific role of each species and its ecology in the epidemiological chain of disease transmission, the accurate identification of flea species and their distributions is of particular importance. Molecular markers can be useful for confirming species identification based on morphological characteristics and have been applied to identify and characterize closely related flea species (Lawrence et al ., , ). One commonly used molecular marker for species identification and phylogenetic analysis of fleas is the cytochrome oxidase subunit I (COI) (Lawrence et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Within this order, the genus Ctenocephalides Stiles & Collins, 1930 is one of the most studied lineages because they tend to parasitize domestic animals such as dogs, cats or other pets which may play an important role as bridging hosts for fleas of different animals (Dobler & Pfeffer, ). Thirteen species and four subspecies are recognized within this genus (Beaucournu & Ménier, ; Lawrence et al , ) out of which Ctenocephalides felis and C. canis have been the most studied species by different authors (Gil Collado, , ; Beaucournu & Launay, ; Lewis, ; Beaucournu & Ménier, ; Ménier & Beaucournu, ; Linardi & Guimarães, ; Durden & Traub, ; Linardi & Santos, ). From a morphological point of view, four subspecies of C. felis have been distinguished: C. felis felis Bouché, 1835, C. felis strongylus Jordan, 1925, C. felis orientis Jordan, 1925 and C. felis damarensis Jordan, 1936 (Hopkins & Rothschild, ).…”
Section: Introductionmentioning
confidence: 99%
“…From a morphological point of view, four subspecies of C. felis have been distinguished: C. felis felis Bouché, 1835, C. felis strongylus Jordan, 1925, C. felis orientis Jordan, 1925 and C. felis damarensis Jordan, 1936 (Hopkins & Rothschild, ). However, only a few studies have been carried out based on molecular data (Vobis et al , ; Marrugal et al , ; Lawrence et al , , ). Thus, some authors have suggested that further molecular studies are needed in order to resolve and elucidate the genetic diversity of C. felis (Lawrence et al , ).…”
Section: Introductionmentioning
confidence: 99%